KEGIATAN ENTREPRENEUR DALAM MENUMBUHKAN KEMANDIRIAN SANTRI DI ERA MODERN - Maulana Fuadi Syah; Khoirul Umam (EL-Islam, 2023)
Abstract: Entrepreneurial activity is an activity in which it teaches creative ways to create an activity that can provide additional knowledge, especially in the world of economics, besides that this activity can provide independence to a student because in it a student is required to be creative and productive. in every activity of his life, including in terms of dividing time between pesantren activities and entrepreneurial activities. The focus of this research includes: 1) Entrepreneurial Activities in Fostering Student Independence in the Modern Era (Case Study at Pondok Pesantren At Tahdzib Ngoro Jombang). 2) Inhibiting and supporting factors of entrepreneurial activity in fostering student independence in the modern era (Case Study at Pondok Pesantren At Tahdzib Ngoro Jombang). This type of research uses a case study approach to find out something in depth. This research is included in qualitative field research. Data collection techniques in this study use interview, observation, documentation and triangulation techniques which are then analyzed. From the results of this study, entrepreneurial activities without us realizing this activity are activities taught by Salafus Sholeh in educating his students with the aim that after graduating from the pesantren world they are able to become independent students, meaning that students returning from boarding schools can practice their religious knowledge from their needs. community, and can have a job from entrepreneurial activities that have been taught from boarding schools (Entreprenuer Skills)